RNLS promotes ovarian cancer growth and inhibits ferroptosis via mediating STAT3 - Liang Lin; Zuolian Xie; Peilin Zhong; Jian Chen; Ning Ma; Ling Li; Li Chen; An Lin (Frontiers in Oncology, 2025)
IntroductionOvarian cancer (OC) is a lethal malignancy for which there are limited therapeutic options. The role of renalase (RNLS) in cancer progression and ferroptosis regulation remains unclear. This study investigates how RNLS mediates STAT3 to promote OC growth and suppress ferroptosis.MethodsRNLS expression was analyzed in OC cell lines (OVCAR3) and normal ovarian epithelial cells (IOSE80) via qPCR. Stable RNLS knockdown (sh-RNLS) and overexpression (ov-RNLS) OVCAR3 models were established via lentiviral infection. STAT3 siRNA was transfected to explore RNLS-STAT3 interactions. Functional assays (CCK8, wound healing, Transwell, flow cytometry) evaluated proliferation, migration, invasion, apoptosis, and ROS levels. Mitochondrial morphology was assessed by electron microscopy. Subcutaneous tumor models in mice validated in vivo effects. Molecular markers (STAT3, p-PI3K/PI3K, p-AKT/AKT, Ki-67, MDA, GPX4, GSH) were analyzed via Western blot, immunohistochemistry, and ELISA.ResultsRNLS was significantly upregulated in OC cells, particularly OVCAR3. RNLS knockdown suppressed STAT3 expression, cell proliferation, migration, invasion, and tumor growth, while promoting apoptosis, ROS accumulation, and mitochondrial damage. Conversely, RNLS overexpression exerted opposing effects. STAT3 silencing inhibited PI3K/AKT signaling and ferroptosis resistance, which were rescued by RNLS overexpression. In vivo, sh-RNLS reduced tumor volume/weight, as well as RNLS/STAT3, Ki-67, GPX4, and GSH, while increasing MDA. ov-RNLS enhanced tumor growth and reversed these molecular changes.ConclusionRNLS drives OC progression by activating STAT3-dependent PI3K/AKT signaling, enhancing proliferation, metastasis, and ferroptosis suppression. Targeting RNLS-STAT3 axis may offer a novel therapeutic strategy against OC.